2006
DOI: 10.1007/s00403-006-0649-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes involved in the regulation of p16 in psoriatic involved skin

Abstract: It has been suggested that the up-regulation of the tumour suppressor p16 gene and induction of senescence protect the phenotype of psoriatic involved skin from malignant transformation. On the other hand, Id1, which is inversely correlated with p16 has been shown to be up-regulated in psoriatic involved skin. To test the hypothesis that there may be an altered regulation of p16 in psoriatic involved skin, we have measured genes involved in the Igf-1 receptor signalling through the Ras/MAPK cascade. Igf-1R, IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 47 publications
4
29
0
Order By: Relevance
“…The increased p16 protein levels in psoriatic lesions have also been reported in the study of Chaturvedi et al [11]. The observed differences in the published data for the p16 gene expression could result from different localization of psoriatic lesions, various age of the plaques and individual features of patients [22].…”
Section: The Role Of the P16 Protein In Psoriasis And Neoplastic Transupporting
confidence: 58%
See 3 more Smart Citations
“…The increased p16 protein levels in psoriatic lesions have also been reported in the study of Chaturvedi et al [11]. The observed differences in the published data for the p16 gene expression could result from different localization of psoriatic lesions, various age of the plaques and individual features of patients [22].…”
Section: The Role Of the P16 Protein In Psoriasis And Neoplastic Transupporting
confidence: 58%
“…Mark et al showed low expression of the p16 encoding gene in the psoriatic plaques as well as in normal skin [22]. Abou et al studied the effect of phototherapy on the p16 expression and found that significantly less protein in psoriatic lesions were observed before phototherapy than in controls.…”
Section: The Role Of the P16 Protein In Psoriasis And Neoplastic Tranmentioning
confidence: 99%
See 2 more Smart Citations
“…INK4A span the exon 1a/exon 2 junction (Mark et al 2006), while the set for p14 ARF target part of exon 1b (Supplementary Table 2, N B Kiss et al: p16 methylation in malignant chromaffin tumors www.endocrinology-journals.org Fig. 1).…”
Section: Cdna Synthesis and Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%